The Inventories, Accounts, and Records of Debts for the Templars’ Estates in England and Wales, 1308-1313, as a Source for the Everyday Lives of the Templars - Nicholson, Helen (Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders, 2025)
Although the inventories, accounts, and records of debts payable and receivable produced for King Edward II of England’s government after the arrests of the Templars in England at the beginning of 1308 are incomplete, they preserve some information on the Templars’ built environment and material culture, the persons living in or associated with Templar properties, religious observance, estate management, and transactions with outsiders. This article uses these data to reconstruct details of the day-to-day lives of the Templars in England just before their arrests, and particularly their relations with non-Templars. Given that the charges brought against the Templars in 1307 alleged that the brothers acted secretly and that non-Templars were unaware of their daily behaviour, evidence they were in fact in daily contact with outsiders undermines the charges and adds to the increasing volume of evidence that the Templars were not guilty as charged. The information from these documents presents a picture of busy communities in which the Templars formed a minority and whose immediate concerns were focussed on local matters, such as employing a priest to support a chantry for a wealthy donor, rather than the distant Holy Land.